THE PROGRAM BUDGET OF THE GOVERNMENT OF THE RUSSIAN FEDERATION - 2020 AND ITS STANDARD OF PROVIDING IN FEDERAL EXECUTIVE AUTHORITIES - Olga E. Bashina; Olga S. Pisetskaya (Статистика и экономика, 2016)
In article the program and target method of control overpublic ﬁnance, and also standard providing the programbudget of the Government of the Russian Federation infederal executive authorities is considered. Advantages of program approach to budgeting of activity of federal executive authorities and additional requirements to stability of thebudgetary system regarding the guaranteed providing withﬁnancial resources of existing account obligations, transparent and competitive distribution of available means atapplication of a program and target method are designated.The main attention is concentrated on the state programswhich purpose is ensuring long-term balance and stabilityof the budgetary system, and also improvement of qualityof management efﬁciency by public ﬁnances.